Raise and characterization of a bread wheat hybrid line (Tulaykovskaya 10 × Saratovskaya 29) with chromosome 6Agi2 introgressed from Thinopyrum intermedium - Yu. N. Ivanova; K. K. Rosenfread; A. I. Stasyuk; E. S. Skolotneva; O. G. Silkova (Вавиловский журнал генетики и селекции)
Wheatgrass Thinopyrum intermedium is a source of agronomically valuable traits for common wheat. Partial wheat–wheatgrass amphidiploids and lines with wheatgrass chromosome substitutions are extensively used as intermediates in breeding programs. Line Agis 1 (6Agi2/6D) is present in the cultivar Tulaykovskaya 10 pedigree. Wheatgrass chromosome 6Agi2 carries multiple resistance to fungal diseases in various ecogeographical zones. In  this work, we studied the transfer of chromosome 6Agi2 in hybrid populations Saratovskaya 29×Tulaykovskaya 10 (S29×T10) and Tulaykovskaya 10×Saratovskaya 29 (T10×S29). Chromosome 6Agi2 was identified by PCR with chromosome-specific primers and by genomic in situ hybridization (GISH). According to molecular data, 6Agi2 was transmitted to nearly half of the plants tested in the F2 and F3 generations. A new breeding line 49-14 (2n = 42) with chromosome pair 6Agi2 was isolated and characterized in T10×S29 F5 by GISH. According to the results of our field experiment in 2020, the line had high productivity traits. The grain weights per plant (10.04±0.93 g) and the number of grains per plant (259.36±22.49) did not differ significantly from the parent varieties. The number of grains per spikelet in the main spike was significantly higher than in S29 (p ≤ 0.001) or T10 (p ≤ 0.05). Plants were characterized by the ability to set 3.77±0.1 grains per spikelet, and this trait varied among individuals from 2.93 to 4.62. The grain protein content was 17.91 %, and the gluten content, 40.55 %. According to the screening for fungal disease resistance carried out in the field in 2018 and 2020, chromosome 6Agi2 makes plants retain immunity to the West Siberian population of brown rust and to dominant races of stem rust. It also provides medium resistant and medium susceptible types of response to yellow rust. The possibility of using lines/varieties of bread wheat with wheatgrass chromosomes 6Agi2 in breeding in order to increase protein content in the grain, to confer resistance to leaf diseases on plants and to create multiflowered forms is discussed.